2013
DOI: 10.1111/jnc.12457
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of neuronal Lysine‐Specific Demethylase 1LSD1/KDM1A impairs transcriptional repression by regulating interaction with CoREST and histone deacetylases HDAC1/2

Abstract: Epigenetic mechanisms play important roles in brain development, orchestrating proliferation, differentiation, and morphogenesis. Lysine-Specific Demethylase 1 (LSD1 also known as KDM1A and AOF2) is a histone modifier involved in transcriptional repression, forming a stable core complex with the corepressors corepressor of REST (CoREST) and histone deacetylases (HDAC1/2). Importantly, in the mammalian CNS, neuronal LSD1-8a, an alternative splicing isoform of LSD1 including the mini-exon E8a, sets alongside LSD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
67
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 85 publications
(75 citation statements)
references
References 52 publications
7
67
0
1
Order By: Relevance
“…Immunoprecipitates with anti-Myc antibodies obtained from 2 mg of whole HEK293 cell extracts were tested for their associated histone deacetylase activity as we described previously (31). Briefly, immunoprecipitates were incubated for 60 min with a short peptide substrate containing an acetylated lysine residue that can be deacetylated by class I, II, and IV HDAC enzymes.…”
Section: Animalsmentioning
confidence: 99%
“…Immunoprecipitates with anti-Myc antibodies obtained from 2 mg of whole HEK293 cell extracts were tested for their associated histone deacetylase activity as we described previously (31). Briefly, immunoprecipitates were incubated for 60 min with a short peptide substrate containing an acetylated lysine residue that can be deacetylated by class I, II, and IV HDAC enzymes.…”
Section: Animalsmentioning
confidence: 99%
“…In mammals, neurospecific splicing of microexon E8a generates the dominant-negative splicing isoform of LSD1 (neuroLSD1), which is required for the acquisition of proper neurite morphology inherent in neuronal maturation (11). Although conventional LSD1 acts as a constitutive repressor through its H3K4 demethylase activity, neuroLSD1 is unable to repress transcription (11,12). It has been shown recently that neuroLSD1 lacks dimethylated H3K4 (H3K4me2) demethylase activity, confirming its role as a dominant-negative LSD1 isoform (13).…”
mentioning
confidence: 99%
“…The neuroLSD1-containing complex also can act as transcriptional activator by acquiring H3K9me2 and H4K20 demethylase activity (13,14). In this context, the finding that LSD1 and neuroLSD1 share a subset of target genes (12)(13)(14) suggests that modulation of exon E8a splicing may represent a mechanism for fine-tuning the transcription of selected targets. The generation of a mouse model lacking microexon E8a (neuroLSD1 KO mice) allowed us to characterize neuroLSD1 as an in vivo modulator of hippocampal excitability.…”
mentioning
confidence: 99%
“…Class II (JmjC domain-containing histone demethylases) are Fe (II) and 2-oxoglutaratedependent demethylases, which reverse lysine mono, di, and trimethylation (Anand and Marmorstein 2007). Recently, many studies found that the functions of HDMs are regulated by post-translational modifications (PTMs) such as methylation, phosphorylation, acetylation, ubiquitination, and sumoylation (Baba et al 2011;Cheng et al 2014;Toffolo et al 2014). KDM4A can also be controlled via post-translational modifications (Tan et al 2011).…”
Section: Introductionmentioning
confidence: 99%